Tinjauan Hukum Kedudukan Informasi Mengenai Situasi Legal Pemohon Suaka Diplomatik dalam Pemberian Suaka Diplomatik Berdasarkan Caracas Convention on Diplomatic Asylum 1954 - Lasman, Lasman (Journal of Contemporary Law Studies, 2025)
This research focuses on addressing one of the gray areas in the practice of diplomatic asylum: the legal standing of information regarding the applicant's legal situation, compiled by the receiving state, and used as a consideration in granting asylum upon the request of the sending state, based on the Caracas Convention on Diplomatic Asylum (1955). In practice, the asylum-granting state has no obligation to allow intervention in evaluating the applicant’s condition. This results in broad discretionary authority for the sending state to unilaterally interpret the legitimacy of diplomatic asylum. This study employs a normative juridical method, relying on literature review and secondary data sources such as relevant international conventions and state practice. The findings show that the Caracas Convention does not explicitly require the receiving state to provide information or allow intervention in the evaluation process conducted by the sending state, nor does it obligate the sending state to request such information.In the absence of legal status information, the sending state may interpret the applicant’s situation based on its own political or legal considerations. This often hampers judicial processes in the receiving state and risks undermining the validity of diplomatic asylum granted to the applicant. As a recommendation, the establishment of a specific international guideline or instrument is necessary to serve as a formal reference for sending states in carefully evaluating the eligibility and status of individuals seeking diplomatic asylum.